2021
DOI: 10.1016/j.paid.2020.110399
|View full text |Cite
|
Sign up to set email alerts
|

The role of empathy in the mechanism linking parental psychological control to emotional reactivities to COVID-19 pandemic: A pilot study among Chinese emerging adults

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) and its worldwide spread have brought economic, social and personal stress. To better understand human adjustments to this public health emergency and its underlying mechanism, the relationship between perceived parental psychological control in emerging adults and individual's emotional reactivity to COVID-19 as well as the role of empathy was examined. The study was conducted among 445 emerging adults using questionnaires measuring parental psychological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 61 publications
3
15
0
Order By: Relevance
“…These results are consistent with available international literature 12,14 and those from the same geographical region as our study 43 . Similarly, as demonstrated by previous research 27,44 , the high objective risk group also consisted of people with more empathic concern compared to the other groups. Finally, even though the risk situation was significantly associated with the acceptance of the lockdown (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…These results are consistent with available international literature 12,14 and those from the same geographical region as our study 43 . Similarly, as demonstrated by previous research 27,44 , the high objective risk group also consisted of people with more empathic concern compared to the other groups. Finally, even though the risk situation was significantly associated with the acceptance of the lockdown (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly and unexpectedly, positive emotions of relaxation and happiness were experienced more frequently and more intensely as compared to the negatively balanced emotions (Moroń & Biolik-Moroń, 2021 ). Similar findings have been reported by Ma and Wang ( 2021 ) who asked participants to rate how much they experience a range of positive versus negative emotions in response to COVID-19. Results revealed that participants experienced positive emotions more frequently than negative ones.…”
Section: Emotions During Covid-19supporting
confidence: 84%
“…More importantly, Moroń and Biolik-Moroń ( 2021 ) found that relaxation and happiness were experienced more frequently and more intensely compared to those negative affective states; that is, increases in positive emotions were particularly pronounced when compared to negative emotions. Ma and Wang ( 2021 ) also found that participants experienced positive emotions more intensely than negative ones. Therefore, the present findings, along with those reported previously (Ma & Wang, 2021 ; Moroń & Biolik-Moroń, 2021 ), suggest that the lockdown-related COVID-19 appear to have changed affective states greatly and in a complicated way with increases in both negative (e.g., fear, anxiety, and distress) and positive (e.g., interest, vigilance, relaxation, and happiness) emotions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other research conducted during the COVID-19 outbreak indicates, however, that empathy levels might fluctuate according to anxiety linked to the risk of death, and this could modulate prosocial willingness (22)(23)(24)(25). Perceived risk of infection have been found to be higher in individuals leaving in locations with higher H1N1 incidence and likely to influence the adherence to disease control measures (26).…”
Section: Introductionmentioning
confidence: 99%